2016
DOI: 10.3906/zoo-1506-21
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical and morphological study of the kidneys of the breeding emu(Dromaius novaehollandiae)

Abstract: We analyzed 16 kidneys obtained from 15-year-old emus, Dromaius novaehollandiae. Emus were kept at an experimental farm in Poland. The results showed that each kidney was composed of 3 parts: cranial, medial, and caudal divisions. Histological results demonstrated that the kidneys consisted of 2 zones: the cortex and the medulla. The cortex made up the majority of the kidney, while the medulla formed only a small portion of the organ. Proximal and distal tubules and 2 types of glomeruli (looped and loopless) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
5
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 12 publications
6
5
0
2
Order By: Relevance
“…Each kidney consisted of three parts(lobes) which were not completely separated (cranial, middle and caudal) (Figure 1). This facts proved what was reported by many others in different birds species, Like what was mentioned by in common coot bird, (17) in Emu, in dove and owl, and (18) in dove, racing pigeon. The result in control group was characterized by (small rounded cranial, round middle and large oval caudal) parts with red brown in color, While in salt stress group, characterized by swollen and congestion in blood vessels (Figure 2).…”
Section: Resultssupporting
confidence: 91%
“…Each kidney consisted of three parts(lobes) which were not completely separated (cranial, middle and caudal) (Figure 1). This facts proved what was reported by many others in different birds species, Like what was mentioned by in common coot bird, (17) in Emu, in dove and owl, and (18) in dove, racing pigeon. The result in control group was characterized by (small rounded cranial, round middle and large oval caudal) parts with red brown in color, While in salt stress group, characterized by swollen and congestion in blood vessels (Figure 2).…”
Section: Resultssupporting
confidence: 91%
“…The present study conducted both the histological and histochemical characteristics of avian kidney and role of the mucopolysaccharid and albumin in protection of urinary system from the effects of urate crystals, in general, all avian species involved in this work, the kidney were lobular organ with wide cortex and small medulla, such a result is consistent with results of (Richardson et al,1991) who studied the kidney of bird from North America, (Sivakumar et al, 2012) in Guinea fowl, (Abdulla et al, 2014) in passer domesticus, (Abood et al, 2014) in harrier, chicken and mallard duck, (Michalek et al, 2016) in breeding emu and (Casotti and Richardson, 1992) who found higher cortical volume in the kidneys of wet zone Honeyeater and in arid zone honeyeaters a higher medullary volume which related with environmental and dietary habits. this result suggest that the high cortical volume in compare to low medulla volume are associated with kidney ability for more urine concentration and water conservation and vice versa (Abood, et al,2014).Our result revealed two types of the renal corpuscles; mammalian type and reptilian type, such observations have recorded by Tsulcamoto et al (2005) in chicken, (Nishimura, 2008) in marine birds, (Michalek et al, 2016) in breeding emu, (Batah, 2012) in coot bird, (Abdulla et al, 2014) in passer domesticus. The most type of the avian nephron was the repitaliane type and there was not more of 30% of the nephron was the mammalian type (Carpenter, 2003;Casotti and Braun, 2000).…”
Section: Discussionsupporting
confidence: 90%
“…In the present result the intermediate type of corpuscle was not observed, this result was as well that of the previous study by (Sivakumar et al, 2012) the intermediate type of corpuscle has recorded by (Mobini and Abdollahi, 2016) in Japanese quail and by (Abood et al, 2014) in Chick &harrier, the reptilian type of renal corpuscles might limit the capacity of the kidney produce hyperosmotic urine and the mammalian corpuscles are essential for concentrated urine (Nishimura and Fan, 2003), this result suggest that, much of the mammalian and intermediate types of corpuscles in breeds are related with birds food habits, so these nephrons play an important role conserving body water. The structure of renal corpuscle was similar to those results mentioned by (Nabipour, 2009, Abood et al, 2014.Other cortical region components were proximal convoluted tubules, distal convoluted tubules, collecting tubules and per lobular collecting ducts along with the many peritubular capillary sinuses, this results concurs (Al-Ajeely and Mohammed, 2012;Sivakumar et al, 2012;Abood et al, 2014;Michalek et al, 2016), (Nabipouret al, 2009).In our results the pariet al layer of Bowman's capsule and the endothelial cells of the capillary tuft basement membranes were delicate structure that reacted positive with PAS stain as described by Sivakumar et al, (2012) in birds and El -Daly(2013) in mammals, this suggested that, the neutral pH of delicate basement membranes of capillaries lead to extruding a fluid from plasma with its electrolyte and water composition as the glomerular filtrate (Cunningham & Klein, 2007). The present result revealed the cytoplasm of epithelial cells and the lumen of proximal convoluted tubules contained positive PAS substances, that indicated the presence of neutral glycoprotein in this part of nephron, this result accord with result revealed that, in of rock dove the lumen of the proximal convoluted tubules contained PAS positive substances (Nabipour 2009;Sivakumar et al, 2012;Sreeranjini et al, 2000;Mobini & Abdollahi, 2016), also this result is compatible with result of (Brandon et al, 2009) in Juvenile American Alligator.On the other hand results of El -Daly,(2013) concluded that, the carbohydrates and proteins have increased after nephrone compartments (glomeruli, basement membrane of the tubules and brush border of proximal tubules) have exposed for green tea in compared to that group which exposed to harmful exogenous substances, this elevation could be due to an increase in the re-absorption of kidney tubules or might be due to an increase in glycogen synthesis or a decrease in glycogen breakdown by phosphorylase, which causes a glycogen recovery in the tissue.…”
Section: Discussionsupporting
confidence: 87%
“…Both the kidneys were placed retroperitoneally symmetrical on either side of the vertebral column in the depression of synsacrum and iliac fossa (Fig 1). The similar findings were reported by Braun and Dantzler (1972) in desert quail, Khadim and Dauod (2014) in barn owl and Michalek et al, (2016) in breeding Emu. Each kidney had dorsal and ventral surfaces.…”
Section: Macroscopicsupporting
confidence: 89%